Brazing of Graphite/Graphite Using a New Filler Technique - Jabur, Adnan S. (Basrah Journal for Engineering Sciences, 2009)
Brazing is one of the best methods of graphite to graphite or to metals joining. But the major problem associating the graphite brazing is the poor wetting by the conventional molten fillers. For this reason, scientists have produced a special filler metal based on active elements which interacts with graphite to form carbides. Also, recently another technique to overcome the wetting problem was introduced by H. Ohmura and T. Yoshida. It included inserting an intermediate layer of pure iron foil inside the copper filler. In the present work, another filler combination of Cu/ steel/Cu foils is proposed as new filler technique for graphite brazing. It was found that, it produced a succeeded joint with a good properties consisted of a columnar phase which resulted from the partially dissolution of iron in molten copper. Additionally, the increasing of brazing time caused reducing the thickness of the steel central layer and increasing the thickness of the columnar phase layers. The x-ray diffraction test developed that, the joints contained two carbide types, iron and copper free elements.